The on-going process of reinventing classic tourism destinations: the case of nordic tourists in Madeira Island - Machado, Luiz Pinto (2020)
In this paper, we analyze the effect of tourism experience-related variables on Nordic visitors’ interest in Madeira as a potential second home destination, within the framework of the reinvention of classic tourism destinations as attractive residential areas and tourism hot spots. Over time, Madeira has experienced a sharp decline in terms of the numbers of Nordic visitors, which has prompted local experts to discuss alternative paths to re-attract past visitors back to the island. The second home market was considered one of the viable solutions among the several alternatives considered to address problems of declining market shares. In order to assess the conditioning factors of success in this market niche, we applied a questionnaire to a sample of Nordic visitors to assess their interest in the local second home market. The econometric approach retained in this study is based on the randomized response to take into account potential bias in the data. We suggest that Nordic visitors are only marginally interested in Madeira for second home purposes, which does not mean that we are dealing with a hopeless situation. Further development in this sector can only be reached in the medium term based on sustained quality improvements along with long-term strategic thinking focused on developing a feeling of attachment among potential second home owners.